Pengaruh Duta Merek NCT dan Citra Merek terhadap Niat Beli Skincare Somethinc - Lawrence, Shania; Setianingsih, Rita Eka (Jurnal Manajemen, 2023)
Currently, the phenomenon of the "Korean Wave" has spread to various parts of the world. Somethinc capitalizes on this phenomenon by recruiting the Korean boy band NCT as the brand ambassador to improve its image. Therefore, brand ambassadors and brand image are the focal points of Somethinc's skincare product marketing campaigns. This research aims to determine whether NCT brand ambassadors and brand image impact the purchase intention of Somethinc skincare products, especially among consumers in Jakarta. Then, the authors collected the data using Google Forms from 120 respondents who knew or had ever bought Somethinc and recruited judgmentally. The data analysis using multiple regression analysis with the help of SPSS 26 reveals that brand ambassadors and brand image positively influence purchase intention. Further researchers can conduct research in different areas.